Large scale synchronous mating and the study of macronuclear development in Euplotes crassus (The Rockefeller University Press, 1985)
After conjugation in hypotrichous ciliates, a new macronucleus is produced from a copy of the micronucleus. This transformation involves large-scale reorganization of DNA, with conversion of the chromosomal micronuclear genome into short, gene-sized DNA molecules in the macronucleus. To study directly the changes that occur during this process, we have developed techniques for synchronous mating of large populations of the hypotrichous ciliate Euplotes crassus. Electron microscope studies show that the micronuclear chromosomes are polytenized during the first 20 h of macronuclear development. The polytene chromosomes lack the band-interband organization observed in other hypotrichs and in the Diptera. Polytenization is followed by transectioning of the chromosomes. We isolated DNA at various times of macronuclear development and found that the average molecular weight of the DNA decreases at the time of chromosome transectioning. In addition, we have shown that a small size group of macronuclear DNA molecules (450-550 base pairs) is excised from the chromosomal DNA approximately 10 h later in macronuclear development.